BURNOUT LEVEL AMONG NURSES: COMPARING PUBLIC TO PRIVATE HOSPITAL IN MANADO - Lombo, Patrisia Anastasia; Lapian, S.L.H.V. Joyce; Tumewu, Ferdinand . (Universitas Sam Ratulangi, 2018)
Abstract: Hospital is an important health care service provider for the community. However, Manado community still complained about how bad the health care service in Manado, they also argue that private hospitalsâ€™ service is better compared to public hospital. Therefore, one of the elements that need to be considered by the hospital in providing quality health care services is the medical staff, and one of the medical staff who is closest to the patient is the nurse, they have a great responsibility for the provision of services to the patients, this great responsibility that faced by nurses make them vulnerable to experiencing job burnout. Therefore, this study aims to find if there is a significant difference in job burnout level among nurses between public and private hospital in Manado. The sample was taken using convenience sampling technique and the sample size of this study was 100 nurses from Bhayangkara Hospital Manado and 100 nurses from GMIM Pancaran Kasih Hospital Manado. The result shows that there is no significant difference in public hospital nurses and private hospital nurses towards the level of job burnout. The human resource manager in each hospital in Manado must pay attention to the medical staff especially the nurses so that they would not experience the job burnout that can affect their performance.Â Keywords: burnout level, public hospital nurses, private hospital nurses